Potential novel markers in IBD and CRC diagnostics. Are MMP-19 and RAGE promising candidates? - Horak, Pavel; Suhaj, Petr; Matej, Radoslav; Cervinkova, Monika (Biomedical papers, 2022)
Aims. Inflammatory bowel diseases and colorectal cancer are serious intestinal disorders with continuously increasing incidence. Many aspects of etiopathogenesis still remain unclear. There is an urgent need to improve early diagnostics and markers indicating the progression of the disease. The aim of our study was to analyze the expression of matrix metalloproteinase-19 (MMP-19), and the receptor for advanced glycation end-products (RAGE) in different cell subpopulations in inflammatory bowel diseases (IBD) and colorectal cancer (CRC) compared to the tissue in the vicinity of pathological processes. Methods. Expression of both markers in epithelium, macrophages and vessels were evaluated in IBD and CRC groups. They were detected using immunohistochemistry in paraffin sections. Results. There were significant differences between the expression of MMP-19 on macrophages and vessels among healthy and cancer tissues. In both, macrophages and vessels were significantly lower levels in cancer tissues. The expression of MMP-19 on vessels was also significantly different between peritumoral and cancer tissues (higher levels in peritumoral tissue). RAGE expression in macrophages was significantly different between healthy and cancer tissues and between peritumoral and cancer tissues. There was significantly lower expression in cancer tissues than in healthy and peritumoral tissues. Expression of RAGE in vessels was significantly different just in the comparison of healthy and peritumoral tissues (higher levels in healthy tissues). Conclusion. Both markers seem to be promising potential auxiliary markers in IBD and CRC diagnostics. They can also improve evaluation of disease progression.
Keywords: inflammatory bowel disease; colorectal cancer; matrix metalloproteinase; receptor of advanced glycation end-products